Trends in cancer incidence and mortality in the process of metropolitanization of Shanghai, 1973–2017 - Qin, Jiejie; Wu, Mengyin; Zhao, Shulin; Gu, Kai; Cai, Renzhi; Tang, Ziwei; Zhu, Defeng; Tian, Jingyan; Yao, Wei; Shen, Baiyong; Shi, Yan (Frontiers in Oncology, 2025)
BackgroundShanghai has become a modern and international metropolis. A more comprehensive understanding of cancer incidence and mortality rates and socioenvironmental factors is explored to develop effective cancer control policies in Shanghai.MethodsCancer registration data are currently collected in Shanghai from 1973 to 2017, and socioenvironmental factors were obtained from the Shanghai statistical yearbook. Multivariate ridge regression analysis explored the contributions of socioenvironmental factors to cancer incidence and mortality, and the estimated annual percentage change (EAPC) was calculated for each cancer type by gender and district.ResultsMultivariate ridge regression analysis indicated that the number of divorces, total waste gas from industry, areas of buildings completed, and number of computers probably drove the increase in cancer incidence, and health expenditure and medical insurance cost probably contributed to the decrease in cancer mortality in Shanghai. Age-standardized cancer incidences of the lung in female patients, prostate, thyroid, and cervix increased most, and the incidence and mortality of esophagus, liver, and stomach cancers decreased most in Shanghai from 2002 to 2017. The most common cancer sites diagnosed were lung, colorectal, female breast, and male prostate in Shanghai in 2017, similar to the pattern in high-income countries. Stricter air control strategies, lower divorce rates, healthier lifestyles, and more effective HPV vaccination campaigns may be useful actionable measures of cancer prevention.ConclusionsThe longitudinal cancer data from the real world, which span decades, reported here and Shanghai’s experience in cancer prevention and control can be a reference for government guidelines in preventing population-level cancer incidence during city development.